Sectoral Concentration in Loans and Credit Risk: An Examination by Company Accounts in Turkey - Elif Acar; Arzu Şahin (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study examines the impact of sectoral concentration on credit default risk, drawing from economic theory and portfolio management principles, utilizing the Turkish aggregated sector-level data and banking data from 2009 to 2022. The study employs a panel data analysis framework to investigate the relationship between sectoral diversification in loans and credit risk, controlling for sector-specific variables. Unlike previous studies primarily reliant on banking system data, this research broadens the scope by incorporating the real sector credit usage data for the measurement of concentration. Additionally, instead of the commonly used Herfindahl-Hirschman Index, the study employs the Sector Concentration Index as a measure of concentration, allowing for a comparison of sector distribution with an ideal market sector distribution. The analysis considers not only the widely used indicator of credit risk, non-performing loans ratio in the banking system but also bad debt ratios in the real sector, thereby enhancing the understanding of credit risk dynamics. The analysis results, which show a significant positive relationship between sectoral concentration indices and non-performing ratios employed, reveal that sectoral credit concentration has an increasing effect on the credit risk level and offers insights into the optimal diversification strategies for mitigating credit risk in the banking sector.